EXAMINING THE EFFECTS OF BRAND IMAGE, ONLINE CUSTOMER REVIEWS, AND GREEN MARKETING ON ONLINE PURCHASE DECISIONS FOR THE BODY SHOP AMONG SHOPEE USERS IN DENPASAR - Ni Kadek Dwi Juniari; I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
Technological developments, especially the internet and social media, have influenced many aspects of people's lives, including how they shop. In Indonesia, marketplace platforms such as Shopee facilitate consumers to buy products online, including beauty products such as body mist. This study aims to analyze the influence of brand image, online customer reviews, and green marketing on the purchase decision of The Body Shop body mist in Denpasar City, Indonesia. Using a quantitative approach, this study collected data from 120 respondents who purchased The Body Shop body mist online. Multiple linear regression analysis showed that brand image, online customer reviews, and green marketing had a positive and significant effect on purchasing decisions. Brand image strengthened consumers' purchase intentions, while online reviews and the implementation of green marketing also increased trust and purchase interest. The results of this study provide insight into the importance of these factors in driving purchasing decisions on e-commerce platforms, particularly Shopee. This study suggests that companies should improve their brand image through education about sustainability, collaborate with influencers to increase positive reviews, and maximize green marketing strategies to boost interest in purchasing The Body Shop body mist products.